Pelatihan Pemanfaatan Smartphone untuk Digital Marketing di SMK Negeri 3 Cimahi - Dini Rohmayani; Arya Aditya; Castaka Agus Sugianto; Ayu Hendrati Rahayu; Aris Haris Rismayana (Yayasan Pemimpin Inovasi Science, 2026)
This community service activity aims to provide training on utilizing smartphones for digital marketing to 70 students of SMK Negeri 3 Cimahi through introducing basic concepts, Shopee features, and practical sessions on creating online stores. The training was conducted on August 23, 2022, using methods of counseling, demonstration, and hands-on practice with participants' smartphones. Results showed high enthusiasm among participants, who successfully understood the material and created their own Shopee stores, thereby enhancing digital entrepreneurship skills in the industry 4.0 era.